A qualitative study on trainees' and supervisors' perceptions of assessment for learning in postgraduate medical education†. (19th April 2013) - Dijksterhuis, Marja G. K.; Schuwirth, Lambert W. T.; Braat, Didi D. M.; Teunissen, Pim W.; Scheele, Fedde
Abstract : Introduction: Recent changes in postgraduate medical training curricula usually encompass a shift towards more formative assessment, or assessment for learning. However, though theoretically well suited to postgraduate training, evidence is emerging that engaging in formative assessment in daily clinical practice is complex. Aim: We aimed to explore trainees' and supervisors' perceptions of what factors determine active engagement in formative assessment. Methods: Focus group study with postgraduate trainees and supervisors in obstetrics and gynaecology. Results: Three higher order themes emerged: individual perspectives on feedback, supportiveness of the learning environment and the credibility of feedback and/or feedback giver. Conclusion: Engaging in formative assessment with a genuine impact on learning is complex and quite a challenge to both trainees and supervisors. Individual perspectives on feedback, a supportive learning environment and credibility of feedback are all important in this process. Every one of these should be taken into account when the utility of formative assessment in postgraduate medical training is evaluated.